1987
DOI: 10.1139/v87-279
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal rearrangement of 2-(tert-butyldimethylsiloxy)-5-methyl-6-exo-[(Z)-3-methyl-1-butenyl]- 4 - exo - vinylbicyclo[3.1.0]hex-2-ene. A total synthesis of (±)-sinularene

Abstract: A total synthesis of the marine sesquiterpenoid (±)-sinularene (1) is described. The alcohol 19 was converted via an 8-step sequence into the bicyclic enone 28. Conjugate addition of lithium divinylcuprate to the latter substance afforded mainly the ketone 30, which was transformed into the enol silyl ether 6. Thermolysis (220 °C, 4.5 h) of 6 provided cleanly the bicyclic triene 7, which, in two steps, was converted into the tricyclic olefinic ketone 34. Hydrogenation of 34 and subsequent Wittig olefination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Since its isolation and determination of its AC through an X-ray study, many racemic syntheses of sinularene 218 were reported to date, however without enantioselective synthesis of this compound. The same finding holds for lemnalol 206 and β-copaene 211 , which were the subject of only racemic syntheses. The biogenetic relationship between the marine sesquiterpenes neopupukeananes and trachyopsanes was ascertained by a biomimetic rearrangement employed as the key step for the enantioselective first total syntheses of the marine sesquiterpenes (−)-2-(formylamino)-trachyopsane 221 and (+)- ent -2-(isocyano)­trachyopsane 223 (Scheme ).…”
Section: Synthesismentioning
confidence: 99%
“…Since its isolation and determination of its AC through an X-ray study, many racemic syntheses of sinularene 218 were reported to date, however without enantioselective synthesis of this compound. The same finding holds for lemnalol 206 and β-copaene 211 , which were the subject of only racemic syntheses. The biogenetic relationship between the marine sesquiterpenes neopupukeananes and trachyopsanes was ascertained by a biomimetic rearrangement employed as the key step for the enantioselective first total syntheses of the marine sesquiterpenes (−)-2-(formylamino)-trachyopsane 221 and (+)- ent -2-(isocyano)­trachyopsane 223 (Scheme ).…”
Section: Synthesismentioning
confidence: 99%
“…Piers and co-workers were the first to examine the DVCPR as a key step in the formal synthesis of (±)-quadrone ( 55 , see Scheme 9 ) [ 49 ], and the total syntheses of sinularene ( 59 ) [ 50 ], prezizanol ( 63 ) and prezizaene ( 64 ) [ 51 ]. The synthesis of the cytotoxic sesquiterpenoid quadrone ( 55 ) from Aspergillus terreus [ 52 53 ] started from tricyclic ketone 52 [ 54 ], which was converted into tricycle 53 in 12 steps.…”
Section: Reviewmentioning
confidence: 99%